2020
DOI: 10.3897/phytokeys.169.57996
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the taxonomy of the Neotropical Haemodoraceae (Commelinales)

Abstract: Based on extensive herbarium, field, botanical illustration, and molecular phylogenetic research, five genera and eight species are recognised for the Neotropical Haemodoraceae. New taxa include Cubanicula Hopper et al., Xiphidium pontederiiflorum M.Pell. et al. and Schiekia timida M.Pell. et al. Two new combinations are made, Cubanicula xanthorrhiza (C.Wright ex Griseb.) Hopper et al. and Schiekia silvestris (Maas & Stoel) Hopper et al. We also correct the author citation for Xiphidium, provide the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…The analyses included both nuclear and plastome data and elucidates the relationship among most lineages, with particular attention paid to seven genera previously unplaced in a molecular phylogenetic context: Aetheolirion , Dictyospermum , Matudanthus , Pseudoparis , Pyrrorhiza , Tapheocarpa , and Triceratella . The two missing genera are Cubanicula , recently described in Haemodoraceae (Pellegrini et al, 2020) and Sauvallea , in Commelinaceae, only known from the type collection (see below).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses included both nuclear and plastome data and elucidates the relationship among most lineages, with particular attention paid to seven genera previously unplaced in a molecular phylogenetic context: Aetheolirion , Dictyospermum , Matudanthus , Pseudoparis , Pyrrorhiza , Tapheocarpa , and Triceratella . The two missing genera are Cubanicula , recently described in Haemodoraceae (Pellegrini et al, 2020) and Sauvallea , in Commelinaceae, only known from the type collection (see below).…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to sample at least one species of each of the 60 currently accepted genera in Commelinales, according to the World Checklist of Vascular Plants (WCVP, 2020, with updates from Pellegrini et al, 2020). Samples were obtained from Royal Botanic Gardens, Kew (RBGK) collections, mainly from the herbarium (K) and the Kew DNA and Kew Tissue Banks, but also from the living collections and the Millennium Seed Bank.…”
Section: Taxon Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocampos et al, 2017, in a tissue-specific occurrence investigation of rhizomes, stems, leaves, flowers, and fruits, confirmed that Schiekia Meisn., an Haemodoraceae previously monospecific genus endemic of South America, is a source of phenylphenalenones [ 23 ]. At that time, the species investigated was treated as Schiekia orinocensis (Kunth) Meisn., but, after a recent taxonomic revision [ 24 ], it is now recognized as Schiekia timida M.Pell., E.J.Hickman, Rhian J.Sm. & Hopper, due to its different ecological preferences and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, this plant composes a drink used in religious ceremonies of the Krahô tribe. S. timida , refers to the “shy” flowers that slightly open mostly during the rainy season of the seasonally flooded grasslands of South America’s north region [ 24 ].…”
Section: Introductionmentioning
confidence: 99%